Redox Targeting of Energy Materials for Energy Storage and Conversion. Issue 25 (1st October 2021) - Zhang, Feifei; Gao, Mengqi; Huang, Shiqiang; Zhang, Hang; Wang, Xun; Liu, Lijun; Han, Ming; Wang, Qing
Abstract: The redox‐targeting (RT) process or redox‐mediated process, which provides great operation flexibility in circumventing the constraints intrinsically posed by the conventional electrochemical systems, is intriguing for various energy storage and conversion applications. Implementation of the RT reactions in redox‐flow cells, which involves a close‐loop electrochemical–chemical cycle between an electrolyte‐borne redox mediator and an energy storage or conversion material, not only boosts the energy density of flow battery system, but also offers a versatile research platform applied to a wide variety of chemistries for different applications. Here, the recent progress of RT‐based energy storage and conversion systems is summarized and great versatility of RT processes for various energy‐related applications is demonstrated, particularly for large‐scale energy storage, spatially decoupled water electrolysis, electrolytic N2 reduction, thermal‐to‐electrical conversion, spent battery material recycling, and more. The working principle, materials aspects, and factors dictating the operation are highlighted to reveal the critical roles of RT reactions for each application. In addition, the challenges lying ahead for deployment are stated and recommendations for addressing these constraints are provided. It is anticipated that the RT concept of energy materials will provide important implications and eventually offer a credible solution for advanced large‐scale energy storage and conversion. Abstract : The redox‐targeting process provides great operation flexibility in circumventing the constraints intrinsically posed by the conventional electrochemical systems. It involves a regenerative close‐loop electrochemical–chemical cycle between an electrolyte‐borne redox mediator and an energy storage/conversion material when implemented in redox‐flow cells, boosting the energy density, and offering an intriguing research platform applied to a variety of chemistries for different applications.